Correlations between body measures with live weight in young male goats - Fonseca, Júlia dos Santos; Pimenta, José Luiz Leonardo de Araujo; Moura, Larissa Sardinha de; Souza, Ludmila Cavati de; Silva, Tatiana Labre da; Fonseca, Carlos Elysio Moreira da; Oliveira, Rodrigo Vasconcelos de (Acta Scientiarum. Animal Sciences, 2021)
Data analysis in goat production, such as those related to body and scrotal measurements, indicate the productive and reproductive animal development. The current study aimed to evaluate the correlations between thoracic perimeter (TP), body length (BL), body compacity (BC), body volume (BV), and scrotal circumference (SC) with body weight (BW) in young male goats of Saanen and Boer breeds. It was used 38 Saanen and 24 Boer male goats, with age average of 7.2 ± 2.0 months. Thoracic perimeter and body length measurements were obtained using a tape measure (cm) and the live weight (kg) a mechanic scale. The variables body compacity (BC) and body volume (BV) were calculated using the equations: and . Boer breed showed live weight and body compacity higher than Saanen breed (p < 0.05). Regarding correlations between biometric measurements and body weight, we did not find any statistical differences between the breeds (p > 0.05). The scrotal circumference presented the lowest association with body weight (p < 0.05). However, all biometric measurements showed highly significant correlations with live body (p < 0.01). In conclusion, thoracic perimeter was the main measure of body weight predictor, considering efficiency and practical aspects.